The Jake Mandell Test as a measure of individual differences in pitch discrimination: validity and reliability properties. - Gustau Olcina Sempere; María-Ángeles P; Mireia Hernández; María Antonia Parcet Ibars; Jacob Mandell; César Ávila (Ediciones Complutense, 2020)
The Jake Mandell Tone Deaf Test (JMT) is an online measure designed to evaluate pitch discrimination in the normal population. The test has been available online since 2006, but no psychometric data have been published. The present research was designed to provide validity and reliability data for this test. Study 1 was conducted in university students, and the performance on the JMT was compared to the AMUSIA online screening tests. Correlations were high with the subtests of the AMUSIA online screening tests, but especially with the Tone discrimination test. Study 2 was conducted in children, and the JMT was compared to different tests of musical abilities. The JMT showed a good relationship with the Tone Discrimination and Rhythm Imitation subtest, but especially with the global score of musical abilities. In addition, the test showed good one-year test-retest reliability. Finally, external validation of the JMT was obtained by noting that musicians obtained higher scores than non-musicians. Discussion is focused on the possibility of using the JMT as a rapid screening measure of individual differences in pitch discrimination in the normal population.